2014
DOI: 10.1038/ki.2014.236
|View full text |Cite
|
Sign up to set email alerts
|

The potential for renoprotection with incretin-based drugs

Abstract: Incretin-based drugs, i.e., glucagon-like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors, are widely used for the treatment of type 2 diabetes. In addition to the primary role of incretins in stimulating insulin secretion from pancreatic β-cells, they have extra pancreatic functions beyond glycemic control. Indeed, recent studies highlight the potential beneficial effects of incretin-based therapy in diabetic kidney disease (DKD). Experimental studies using various diabetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 104 publications
2
89
0
2
Order By: Relevance
“…Конечные продукты гликирования (КПГ) индуцируют развитие окислительного стресса, системно-го воспаления, фиброза, апоптоза в культуре мезангиаль-ных клеток за счет активации таких агентов, как фактор роста эндотелия сосудов, MCP-1 [31]. В эксперименталь-ных работах продемонстрировано ингибирующее влия-ние ГПП-1 на экспрессию МСР-1 и рецептора КПГ в культуре мезангиальных клеток, ингибирование процес-сов системного воспаления и окислительного стресса [32,33]. В экспериментах на лабораторных крысах с СД-1 применение эксендина-4 способствовало уменьшению альбуминурии, гипертрофии клубочков, макрофагальной инфильтрации клубочков, снижению развития фиброза и тубулопатии вне зависимости от уровня глюкозы в крови [34].…”
Section: Discussionunclassified
“…Конечные продукты гликирования (КПГ) индуцируют развитие окислительного стресса, системно-го воспаления, фиброза, апоптоза в культуре мезангиаль-ных клеток за счет активации таких агентов, как фактор роста эндотелия сосудов, MCP-1 [31]. В эксперименталь-ных работах продемонстрировано ингибирующее влия-ние ГПП-1 на экспрессию МСР-1 и рецептора КПГ в культуре мезангиальных клеток, ингибирование процес-сов системного воспаления и окислительного стресса [32,33]. В экспериментах на лабораторных крысах с СД-1 применение эксендина-4 способствовало уменьшению альбуминурии, гипертрофии клубочков, макрофагальной инфильтрации клубочков, снижению развития фиброза и тубулопатии вне зависимости от уровня глюкозы в крови [34].…”
Section: Discussionunclassified
“…DPP-4 inhibits hemopoietic factors such as G-CSF or erythropoietin, and it has been reported that the antagonism is inhibited by a DPP-4 inhibitor [16][17][18]. Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is hard to cause the weight gain too [9]. It has been reported to exert a kidney protection effect and is expected as the new drug of choice in diabetes treatment where there is decreased renal function [10][11][12][13][14][15][16]. Recently, DPP-4 inhibits hemopoietic factors such as granulocyte-colony stimulating factor (G-CSF) or erythropoietin, and it is reported that the antagonism is inhibited by DPP-4 inhibitors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is uncertain whether this finding relates to the direct effects of liraglutide on kidney function. 21,22 More patients in the liraglutide group than in the placebo group permanently discontinued the trial regimen owing to adverse events (difference, 2.2 percentage points). There has been considerable interest in a potential association between the use of GLP-1-receptor agonists and pancreatitis and pancreatic cancer, although there is no consistent preclinical, pharmacovigilance, or epidemiologic evidence to date.…”
mentioning
confidence: 99%